2016
DOI: 10.1007/s10459-016-9666-9
|View full text |Cite
|
Sign up to set email alerts
|

E-learning optimization: the relative and combined effects of mental practice and modeling on enhanced podcast-based learning—a randomized controlled trial

Abstract: Enhanced podcasts increase learning, but evidence is lacking on how they should be designed to optimize their effectiveness. This study assessed the impact two learning instructional design methods (mental practice and modeling), either on their own or in combination, for teaching complex cognitive medical content when incorporated into enhanced podcasts. Sixty-three medical students were randomised to one of four versions of an airway management enhanced podcast: (1) control: narrated presentation; (2) modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 41 publications
0
33
0
2
Order By: Relevance
“…Integration and adaptation must prevail in any learning approach. On the other hand, neuroscience and cognition especially in inhibitory:excitatory (I:E) balance synapses [43] concerning neuroplasticity, should be better understood to optimize the strategy of Targeted Neuroplasticity Training (TNT). By achieving better understanding of cognition and metacognition with neuroimaging, we feel global knowledge will evolve on two fronts : 1-Precision in education with personalized cognition and 2-With combined utilization of neuroscience, artificial intelligence and metacognition evolution will reach for solving the recent asymptote curve of expertise but not without a strict necessity of neuroethics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integration and adaptation must prevail in any learning approach. On the other hand, neuroscience and cognition especially in inhibitory:excitatory (I:E) balance synapses [43] concerning neuroplasticity, should be better understood to optimize the strategy of Targeted Neuroplasticity Training (TNT). By achieving better understanding of cognition and metacognition with neuroimaging, we feel global knowledge will evolve on two fronts : 1-Precision in education with personalized cognition and 2-With combined utilization of neuroscience, artificial intelligence and metacognition evolution will reach for solving the recent asymptote curve of expertise but not without a strict necessity of neuroethics.…”
Section: Discussionmentioning
confidence: 99%
“…Among the enhancement literature, Hardy et al proved the effect of cognitive enhance learning (Videogame Lumosity) in the Grand Index Score being enhanced in speed of processing, short term memory, working memory, problem solving and fluid reasoning assessments [42]. Alam and Leblanc have shown that multiple choice scores can be optimized with E-learning sessions by combining mental practice with modeling [43]. Several combinations of enhancement are possible and the operation strategy must be studied in different situations.…”
Section: Mental Practice and Neuroenhancersmentioning
confidence: 99%
“…Among the enhancement literature, Hardy et al [42] proved the effect of cognitive enhance learning (Videogame Lumosity) in the Grand Index Score being enhanced in speed of processing, short term memory, working memory, problem solving and Building towards Expertise in CME (Continuous Medical Education): Suggestions for a New Paradigm 107 fluid reasoning assessments 42. Alam et al [43] have shown that multiple choice scores can be optimized with "e-learning" sessions by combining mental practice with modeling 43. Several combinations of enhancement are possible and the operation strategy must be studied in different situations.…”
Section: Mental Practice and Neuro-enhancersmentioning
confidence: 99%
“…Anesthesia podcast users report the need for a wide range of topics available as debates, journal article summaries, and mostly of short duration and multiple media [ 20 ]. The development and success of a podcast series may be influenced by the availability of content that meets the target user’s needs and inclusion of various evidence-based models for knowledge transfer and retention [ 21 - 27 ]. There is currently no published data on the scope of podcasts in anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in this growing area of e-resources for anesthesia, it is worthwhile defining and determining the factors that make for a successful podcast series. The importance of peer review and reliability of sources creating podcasts have been reported to influence their use and adoption [ 20 , 27 ]. There is also currently no published literature on the peer-review process for anesthesia podcasts.…”
Section: Introductionmentioning
confidence: 99%